Edge-fault-tolerant pancyclicity of 2-tree-generated networks. Issue 3 (2nd October 2019) - Abdallah, Mohamad
ABSTRACT: Jwo et al. introduced the alternating group graph as an interconnection network topology for computing systems. A graph is pancyclic if it contains cycles of all possible lengths. P-Y Tsai et al. showed that the alternating group graph A G n is pancyclic, and remains pancyclic after the deletion of 2 n −6 edges. In this paper we consider a class of Cayley graphs introduced by Cheng et al. that are generated by certain 3-cycles on the alternating group A n . These graphs are generalizations of the alternating group graph A G n . We look at the case when the 3-cycles form a 'tree-like structure', and analyse the pancyclicity of these graphs. We prove that this family of Cayley graphs is ( 2 n − 6 ) -edge-fault-tolerant pancyclic.